Effect of harvest stage on engineering, physio-chemical, bioactive and drying properties of turmeric - Shaik Jakeer Basha; Kamaljit Kaur; Prabhjot Kaur; Tarvinder Pal Singh (Technology in Horticulture)
Fresh turmeric rhizomes (var. Punjab Haldi-1 and Punjab Haldi-2) harvested at the early stage and harvest stage were evaluated for engineering, physio-chemical, and bioactive properties. Determination of engineering properties of agricultural produce (turmeric) plays a significant role in designing machines for processing, grading, separation, storage, and packaging systems. The stage of harvest significantly affected the engineering, bioactive, and physio-chemical properties of fresh turmeric rhizomes. Early harvest rhizomes of both varieties were irregular in growth, immature, and poor in nutritional value as compared to the harvest stage. Geometric properties increased with variation in the size and moisture content of rhizomes. Gravimetric and frictional properties of rhizomes at the harvest stage resulted in higher values which play key roles in bulk packaging, transport, and storage. The harvest stage didn't show any significant effect on optical properties. Rhizomes of Punjab Haldi-2 variety at the harvest stage resulted in superior properties, with high curcumin (4.52%), total phenols (52.06 mg GAE/100 g), and antioxidant activity (45.92% inhibition). Processing conditions (blanching and pressure cooking) altered the physical, functional and bioactive profile of turmeric powder. Turmeric powder processed by blanching at 70 °C for 15 min exhibited better optical properties and bioactive composition with minimal loss of curcumin and total phenols rather than pressure cooking. The functional and physical properties of turmeric powder improved on processing at higher temperatures for a longer time. Thus, the knowledge gained in this study will facilitate grading, transporting, packaging, and sorting, help in the reduction of harvest losses, and designing of equipment for turmeric processing.